The Burdwood Bank Circulation - Matano, Ricardo P.; Palma, Elbio Daniel; Combes, Vincent (Journal of Geophysical Research: Oceans)
A suite of high-resolution numerical simulations characterizes the oceanic circulation in the Burdwood Bank, a shallow seamount located in the northeastern end of the Drake Passage. Model analysis shows energetic upwelling and mixing uplifting deep and benthic waters into the photic layer. Tides and the Antarctic Circumpolar Current are the primary drivers of the bank's circulation. Tidal forcing is the main driver for the entrainment of deep waters into the upper layers of the bank and local wind forcing for the detrainment of these waters into the deep ocean. Passive tracer diagnostics suggest that the dynamical processes triggered by the Burdwood Bank could have a significant impact on local ecosystems and the biogeochemical balance of the southwestern Atlantic region, which is one of the most fertile portions of the Southern Ocean. Model results are robust—they are reproduced in a wide array of model configurations—but there is insufficient observational evidence to corroborate them. Satellite color imagery does not show substantial chlorophyll blooms in this region but it shows strong phytoplankton plumes emanating from the bank. There are several potential explanations for the chlorophyll deficit, including lack of light due to persistent cloud cover, deep mixing layers, fast ocean currents, and the likelihood that blooms, while extant, might not develop on the surface. None of these possibilities can be confirmed at this stage. Fil: Matano, Ricardo P. State University of Oregon; Estados Unidos Fil: Palma, Elbio Daniel. Universidad Nacional del Sur. Departamento de Física; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Bahía Blanca. Instituto Argentino de Oceanografía. Universidad Nacional del Sur. Instituto Argentino de Oceanografía; Argentina Fil: Combes, Vincent. State University of Oregon; Estados Unidos